Icthyofaunal Diversity in Jagannath University New Campus Area, Keraniganj, Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2023)
The study was carried out to know the ichthyofaunal diversity in Jagannath University new campus area from August 2020 to March 2021. A great variety of fish species were recorded from 15 diversified families. Among those, Cyprinidae was the most species-rich family, have 7 species. Total 29 fish species were identified; among them, the dominant order is Anabantiformes comprises of 9 species. Identified species mostly under least concern (20) category, Channa marulius (Hamilton, 1822) are the only endangered species, 1 species under vulnerable category, 4 species belong to near threatened. Three invasive species were recorded from this area, which is very alarming for native fish diversity. Gears and crafts were seen to: cast net, lift net, drag net, gill net, and chai, polo observed in the study area. Some pollution sources were also identified during the study period.Bangladesh J. Zool. 51(2): 165-173, 2023